FLOW MODELING IN SIDE CHANNEL SPILLWAYS USING THEORETICAL AND NUMERICAL METHODS BASED ON COMPUTATIONAL FLUID DYNAMICS - Dhitaisma, Elsya; Dermawan, Very; Sisinggih, Dian (Jurnal Rekayasa Mesin, 2025)
The spillway is a critical structure in dam projects. Failure to manage extreme flood events, like the Probable Maximum Flood (QPMF), may cause overtopping and dam failure. This study examines the hydraulic characteristics of the Surumana Dam's side channel spillway in Central Sulawesi, Indonesia, using Computational Fluid Dynamics (CFD) through ANSYS FLUENT. Initial calibration is based on water surface elevation above the spillway, with a relative error below 5%, confirming the model's accuracy. For Q₁₀₀th, the flow corresponds to free flow, while for QPMF, it exhibits submerged flow, with no cavitation. The overall model performance is evaluated using the Brier-Skill Score (BSS), with scores of 0.812 for Q₁₀₀th (excellent) and 0.795 for QPMF (good) for water surface elevation. Similarly, flow velocity BSS scores are 0.923 for Q₁₀₀th and 0.823 for QPMF, both rated excellent. These results demonstrate that the CFD model reliably represents hydraulic behavior under various flow conditions.